Ungkapan Ūlū Al-Albāb menurut Mufasir - Syukran Abu Bakar; Putri Balqis (TAFSE: Journal of Qur'anic Studies, 2020)
The Qur'an is a holy book that contains a discussion of many things, one of which is related to reason, namely ulū al-albāb. The word ulū al-albāb is mentioned 16 times in the Qur'an. Ulū al-albāb means people who have a reason or use reason. In the Indonesian translation, the term ulū al-albāb is defined as intelligent people or people who have common sense, while interpreters (mufasir) give a general and different meaning to the word ulū al-albāb. On this basis, it is necessary to conduct an in-depth study of the meaning of ulū al-albāb, so that it can be known in detail the meaning of ulū al-albāb according to the views of interpreters. This study is bibliographic in nature and the data collection is carried out thematically (mauḍū'i). The results showed that the interpreters gave different meanings regarding the term ulū al-albāb. SayyidQutb explained that ulū al-albāb are the people who first received direction to taqwa, while according to M. QuraishShihab it means people who have pure reason (a mind that is clean from lust), while al-Maraghi defines ulū al-albāb with people who understand and maintain the meaning of life, the secrets and wisdom of enforcing the law, and the benefits contained in the law. The duties and responsibilities of ulū al-albāb are to disseminate knowledge to lead society and foster the morals of Muslims. Alquran merupakan kitab suci yang memuat pembicaraan banyak hal, salah satu pembicaraannya berkenaan dengan akal, yaitu ūlū al-albāb. Kata ūlū al-albāb disebutkan sebanyak 16 kali dalam Alquran.Secaralahirūlū al-albābberarti orang yang mempunyai akal atau menggunakan akal.Dalam terjemahan Indonesia, istilah ūlū al-albāb diartikan dengan orang-orang yang berakal atau orang-orang yang mempunyai akal sehat, sedangkan mufasirmemberi pemaknaan terhadap kata ūlū al-albāb  secara umum dan berbeda. Atas dasar tersebut, perlu dilakukan kajian mendalam tentang makna ūlū al-albāb, sehingga dapat diketahui dengan detail maknaūlū al-albābmenurut pandangan ulama tafsir. Kajian ini bersifat kepustakaan dan dalam pengumpulan data dilakukan secara mauḍū’i (tematik). Hasil penelitian menunjukkan bahwa para mufasirmemberikan pengertian yang berbeda-beda terkait istilah ūlū al-albāb. Sayyid Quthb menjelaskan bahwa ūlū al-albābyaitu orang-orang yang pertama kali mendapat pengarahan kepada taqwa, sedangkan menurut M. Quraish Shihab mengartikannya dengan orang yang mempunyai akal murni (akal yang bersih dari hawa nafsu), sementara al-Maraghi ūlū al-albābmendefinisikannya dengan orang yang mengerti dan memelihara arti kehidupan, mampu memahami rahasia dan hikmah ditegakkannya hukum, mereka mampu memahami maslahat yang terdapat didalam hukum. Tugas dan tanggung jawab ūlū al-albābadalahmenyebarluaskan ilmu pengetahuan dalam rangka memimpin masyarakat dan membina akhlak umat Islam.